Pilot Scale Elimination of Phenolic Cellulase Inhibitors From Alkali Pretreated Wheat Straw for Improved Cellulolytic Digestibility to Fermentable Saccharides - Haq, Ikram ul; Nawaz, Ali; Liaqat, Badar; Arshad, Yesra; Fan, Xingli; Sun, Meitao; Zhou, Xin; Xu, Yong; Akram, Fatima; Jiang, Kankan (Frontiers in Bioengineering and Biotechnology, 2021)
Depleting supplies of fossil fuel, regular price hikes of gasoline and environmental deterioration have necessitated the search for economic and eco-benign alternatives of gasoline like lignocellulosic biomass. However, pre-treatment of such biomass results in development of some phenolic compounds which later hinder the depolymerisation of biomass by cellulases and seriously affect the cost effectiveness of the process. Dephenolification of biomass hydrolysate is well cited in literature. However, elimination of phenolic compounds from pretreated solid biomass is not well studied. The present study was aimed to optimize dephenoliphication of wheat straw using various alkalis i.e. Ca(OH)2 and NH3; acids i.e. H2O2, H2SO4, H3PO4; combinations of NH3+ H3PO4 and H3PO4+ H2O2 at pilot scale to increase enzymatic saccharification yield. Among all the pretreatment strategies used, maximum reduction in phenolic content was observed as 66 mg Gallic Acid Equivalent/ gram Dry Weight (GAE/g DW), compared to control having 210 mg GAE/g DW using 5% (v/v) combination of NH3+H3PO4. Upon subsequent saccharification of dephenoliphied substrate, the hydrolysis yield was recorded as 46.88%. Optimized conditions such as using 1%+5% concentration of NH3+ H3PO4, for 30 min at 110℃ temperature reduced Total Phenolic Content (TPC) to 48 mg GAE/g DW). This reduction in phenolic content helped cellulases to act more proficiently on the substrate and saccharification yield of 55.06% was obtained.The findings will result in less utilization of cellulases to get increased yield of saccharides by hydrolyzing wheat straw, thus, making the process economical. Furthermore, pilot scale investigations of current study will help in upgrading the novel process to industrial scale.